Participatory technology development in tuber crops - Ramanathan, S.; Anantharaman, M.; Sivakumar, P. Sethuraman (Indian Horticulture, 2019)
Thus, PTD approach involving the user system in the varietal evaluation appears to hasten the process of technology testing and dissemination. In addition, feedback obtained helps the researchers to target research towards demand-driven priorities as well as refine the generated technologies to make them suitable to clientele system.